Integrasi Nilai-Nilai Pendidikan Agama Islam Pada Mata Pelajaran Prakarya Kewirausahaan Dan Ekonomi Di SMAN 1 Sungayang - Kurnia Fitri Andani; Fadriati (Qalam : Jurnal Ilmu Kependidikan, 2023)
This study examines the integration of Islamic Religious Education (PAI) subjects with entrepreneurship (PKWU) and economics. The problem in this study is the rise of dichotomy of knowledge in public education which separates religious knowledge from general science. This causes misunderstandings and fragmentation of students' knowledge. This research is a field research using a qualitative approach. Data collection was carried out by observation, structured interviews and documentation. Data analysis used the Miles and Huberman analysis technique which consisted of three stages namely; data reduction, presentation, and verification. The results of the study stated that there was strong integration between Islamic Religious Education (PAI) subjects and entrepreneurship and economics craft subjects. This can be seen from the internalization of the values of Islamic religious education in economics subjects and entrepreneurial crafts, especially in the material principles and economic practices in Islam. This can be seen from the learning process and products produced by students in craft and entrepreneurship subjects as well as the economic principles taught. In addition, there are also marketing day activities and traditional food bazaars which are held according to Islamic law. Keywords : Integration, Craft and Entrepreneurship, Economy